Worlds of music an introduction to the music of the world's peoples - Titon, Jeff Todd; Cooley, Timothy J.; Locke, David; Rasmussen, Anne K.; Reck, David B.; Scales, Christopher A.; Schechter, John M.; Stock, Jonathan P.J.; Sutton, R.Andreson (Boston Cengage Learning, 2017)
Provides authoritative, accessible coverage of the world's music cultures. Based on the authors' fieldwork and expertise, this text presents in-depth explorations of several music cultures from around the world, with new chapters on China, Eastern Europe and the Arab world. The student-friendly, case-study approach and music-culture focus gives students a true sense of both the music and the culture that created it.
The music-culture as a world of music -- North America/Native America -- Africa/Ewe, Mande, Dagbamba, Shona, BaAka -- North America/Black America -- Europe/Central and Southeastern Regions -- Asia/India -- Asia/Indonesia -- Asia/China, Taiwan, Singapore, Overseas Chinese -- South America/Chile, Bolivia, Ecuador, Peru -- The Arab World -- Discovering and Documenting a World of Music.
Includes bibliographical references, discographies, videographies, and index.
Keywords: World music -- History and criticism; Ethnomusicology